2005
DOI: 10.1128/jcm.43.11.5660-5664.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clonal Complexity in Tuberculosis by Mycobacterial Interspersed Repetitive Unit-Variable-Number Tandem Repeat Typing

Abstract: In recent years, the application of molecular tools has shown us that clonal complexity in infection byMycobacterium tuberculosis is not anecdotal. Exogenous reinfections, mixed infections, compartmentalization, and microevolution are different aspects of this issue. The detection and characterization of clonal variants of M. tuberculosis by standard genotyping methods is laborious and frequently requires expertise. Our aim was to evaluate a new genotyping PCR-based method for M. tuberculosis, mycobacterial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…limit of mixed templates for our PCR assays was estimated to be 1:26 to 1:40, compared with a reported 1:99 detection limit for MIRU-VNTR typing (11).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…limit of mixed templates for our PCR assays was estimated to be 1:26 to 1:40, compared with a reported 1:99 detection limit for MIRU-VNTR typing (11).…”
Section: Discussionmentioning
confidence: 67%
“…However, it is possible that, had we the means to investigate all samples in this study by also using MIRU-VNTR typing, we may have identified more mixed infections. Of the 3 most commonly used techniques for genotyping M. tuberculosis isolates (IS6110-RFLP, spoligotyping, and MIRU-VNTR typing), it is MIRU-VNTR typing that has the greatest capacity to detect the presence of multiple strains, as has been previously demonstrated (11,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot completely rule out the possibility of undetected polyclonal infection, since we did not genotype more than one isolate per episode in all cases. It is also possible that mixed infection remained undetected by MIRU; however, such a scenario seems improbable, since the percentage of one of the strains would have to be lower than 1% (9). Despite these limitations, to the best of our knowledge, this is the first study to experimentally address the hypothesis of possible misassignment of reinfections due to undetected polyclonal infection.…”
Section: Discussionmentioning
confidence: 95%
“…The new PCR-based technique MIRU-VNTR has proven to be a faster, simpler, and more efficient approach for the identification of clonal complexity (9). Combination of MIRU-VNTR with analysis of several serial isolates per patient has been recommended to improve detection of clonal heterogeneity and to minimize underestimation of clonally complex infections (19).…”
Section: Discussionmentioning
confidence: 99%
“…If XDR-TB becomes increasingly prevalent within nosocomial settings in Tomsk, time spent in these facilities could, in the future, become associated with risk of infection or reinfection with XDR-TB, as has been observed in other epidemic locations (22). In addition to reinfection during MDR treatment, it is also possible that heteroresistance (clonal heterogeneity with subpopulations of MDR and XDR variants) (23) or mixed infection with different MDR and XDR strains were present at baseline (24)(25)(26)(27). If the XDR strains were relatively rare within an individual, standard drug resistance testing may not have detected XDR that was present at the time of treatment initiation for MDR disease.…”
Section: Discussionmentioning
confidence: 99%